Partial preservation of chiral symmetry and colossal magnetoresistance in adatom doped graphene - Usaj, Gonzalo (2014)
We analyze the electronic properties of adatom-doped graphene in the low-impurity-concentration regime. We focus on the Anderson localized regime and calculate the localization length ξ as a function of the electron doping and an external magnetic field. The impurity states hybridize with carbon's p z states and form a partially filled band close to the Dirac point. Near the impurity band center, the chiral symmetry of the system's effective Hamiltonian is partially preserved, which leads to a large enhancement of ξ . The sensitivity of transport properties, namely, Mott's variable range hopping scale T 0 , to an external magnetic field perpendicular to the graphene sheet leads to a colossal magnetoresistance effect, as observed in recent experiments.